Learning Cycle-6e and Cognitive Conflict Strategies: The Remedial Learning to Overcome Misconceptions - Jeharut, Rolisonia Rona Kecima; Subandi, Subandi; Habiddin, Habiddin (Universitas Negeri Malang, 2020)
The purposes of this study were to identify students' misconceptions on acid-base concepts; examine the effectiveness of the Learning Cycle-6E models and cognitive conflict strategies in overcoming students' misconceptions; measure the retention of students' understanding of the concept. A descriptive and pre-experimental design with one group pretest-posttest design was employed in the study. 30 secondary school students from a public school in the province of Nusa Tenggara Timur, Indonesia. A three-tier instrument was applied to reveal students’ misconceptions as well as their scientific understanding. A paired t-test stastical procedure was apllied to uncover the effectiveness of the Learning Cycle-6E and cognitive conflict strategies. The retention of students' conceptual retention was measured in 3 weeks after the intervention (the implementation of Learning Cycle-6E models and cognitive conflict strategies). Several students’ misconception in the topic of acid-base have been uncovered. Also, that Learning Cycle-6E and cognitive conflict strategies are powerful in reducing misconceptions is proven. This paper also highlights that retention of students scientific understanding was also in very good criteria